"Namaste Flap": Modification of Subcutaneous Pedicle Propeller Flaps in the Reconstruction of Postburn Axillary and Elbow Contractures. Issue 6 (December 2019) - Karki, Durga; Muthukumar, Vamseedharan; Dash, Suvashis
Abstract : Introduction: The reconstruction of the postburn contracture area is always a challenge in the field of plastic surgery. Moreover, the joints are very sensitive to trauma and immobilization, showing a susceptibility to stiffness. The aim of this article is to emphasize the use of "Namaste flap"—modification of subcutaneous pedicle propeller flaps in the reconstruction of postburn axillary and elbow contractures. Methodology: This is a prospective case study of axillary and elbow contractures managed at a tertiary care hospital using Namaste flap—modification of subcutaneous pedicle propeller flaps from 2010 to 2016. The surgical technique involved raising 2-limbed subcutaneous pedicle-based propellar flap over the contracture using the unburnt skin at the axillary and cubital fossa. The flap with both the limb thus raised was rotated by 90 degrees in the same direction and inserted into the defect. Results: Nine patients including 6 patients with elbow and 3 patients with axillary contractures were included in this study. The mean degree of contracture in axilla and elbow was 78.3 degrees and 59.1 degrees, respectively. The functional results postoperatively were satisfactory. The mean postoperative degree of joint movements in axilla and elbow was 176.3 degrees and 173.6 degrees, respectively. No major complications were encountered. There was a mean period of 12 months of follow-up. Conclusions: In cases where normal skin is still present on the axillary and cubital fossa with scar contracture caused by extensive burns, the subcutaneous propeller flap methods and their modifications should be considered one of the most useful versatile reconstruction methods. Namaste flap in addition to the advantages of subcutaneous pedicle propeller flap also negates the disadvantages caused by the use of split skin grafting of the donor area.